Radiotherapy for early non-melanoma skin cancer. (November 2019) - Chua, Benjamin; Jackson, James E.; Lin, Charles; Veness, Michael J.
Highlights: Radiotherapy is important the management of nonmelanoma skin cancer. Efficacy and side-effects of radiotherapy for skin cancer are well established. Novel techniques improve access and quality of radiotherapy for skin cancer. Abstract: This article reviews the important role of radiotherapy in the management of early non-melanoma skin cancer, in the definitive and adjuvant settings. Therapeutic considerations and appropriate patient selection will be discussed, as well as evidence for efficacy and potential side-effects. Additionally, we present some recent advances which may improve accessibility and quality of radiotherapy, such as more convenient dose-fractionation, wide-field treatments, electronic brachytherapy and 3D printed bolus.